2009
DOI: 10.1007/s12526-009-0029-0
|View full text |Cite
|
Sign up to set email alerts
|

Deep-sea nematode assemblages of the Clarion-Clipperton Nodule Province (Tropical North-Eastern Pacific)

Abstract: The deep-sea nematode assemblages of the French mining claim area in the Clarion-Clipperton Nodule Province (the Northeastern Pacific Basin, 14°N, 130°W, depth 4,947-5,046 m) were studied at species, genus and family levels. Material was obtained using multicorers and box corers. In total, 2,174 individuals from 14 stations and 21 samples were examined. The nematode assemblages from the nodule-bearing (NB) part of the sampling area differed significantly from those at the nodule-free (NN) section. The averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
64
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 35 publications
12
64
1
2
Order By: Relevance
“…In addition to the physical disturbance due to mineral deposit extraction, the reduction in habitat heterogeneity (Zeppilli et al 2014) may permanently alter the structure of benthic communities (Leduc et al 2015 and references therein). Benthic meiofauna from polymetallic nodule areas are known from the Pacific Ocean (Hessler and Jumars 1974;Snider et al 1984;Renaud-Mornant and Gourbault 1990;Bussau et al 1995;Ahnert and Schriever 2001;Radziejewska 2002;Lambshead et al 2003;Veillette et al 2007a, b;Miljutin and Miljutina 2009a, b;Miljutina et al 2010Miljutina et al , 2011Miljutina and Miljutin 2012) and Indian Ocean (Parulekar et al 1982;Ansari 2000;Ingole et al 2000Ingole et al , 2005Singh et al 2014). The techniques used for the extraction of nodules from the seafloor involve mechanical screening, bucket or scraper methods or hydraulic approaches to lift the nodules from the seafloor (Thiel 2003).…”
Section: Exploitation Of Mineral Resourcesmentioning
confidence: 99%
“…In addition to the physical disturbance due to mineral deposit extraction, the reduction in habitat heterogeneity (Zeppilli et al 2014) may permanently alter the structure of benthic communities (Leduc et al 2015 and references therein). Benthic meiofauna from polymetallic nodule areas are known from the Pacific Ocean (Hessler and Jumars 1974;Snider et al 1984;Renaud-Mornant and Gourbault 1990;Bussau et al 1995;Ahnert and Schriever 2001;Radziejewska 2002;Lambshead et al 2003;Veillette et al 2007a, b;Miljutin and Miljutina 2009a, b;Miljutina et al 2010Miljutina et al , 2011Miljutina and Miljutin 2012) and Indian Ocean (Parulekar et al 1982;Ansari 2000;Ingole et al 2000Ingole et al , 2005Singh et al 2014). The techniques used for the extraction of nodules from the seafloor involve mechanical screening, bucket or scraper methods or hydraulic approaches to lift the nodules from the seafloor (Thiel 2003).…”
Section: Exploitation Of Mineral Resourcesmentioning
confidence: 99%
“…Nevertheless, the value of this work is still enormous because of its completeness and carefulness. Many of Bussau's species were rediscovered 5,200 km from their original location (Miljutina et al 2010). The other example in this context is the set of Vitiello's papers that contain descriptions of 85 species from the upper slope of the Mediterranean (Vitiello 1969a(Vitiello , b, 1970a(Vitiello , b, c, d, 1971(Vitiello , 1975(Vitiello , 1976Vitiello and Haspeslagh 1972).…”
Section: Historical Review Of Deep-sea Nematode Studiesmentioning
confidence: 99%
“…The species richness of these communities has exceeded all scientific expectations, especially the high diversity of marine nematodes. For example, from 200 to 325 nematode morphotypes were identified in samples of about 2,000 individuals from different abyssal regions (Bussau 1993;Lambshead et al 2003;Miljutina et al 2010), and 246 nematode genera were found in a total sample of 18,000 individuals from a deep-sea nodule field of the ClarionClipperton Fracture Zone (Pacific) (Radziejewska et al 2001; Dr. V.V. Galtsova, pers.…”
Section: Introductionmentioning
confidence: 99%
“…The community structure of abyssal megafauna and macrofauna in manganese nodule fi elds was found to differ not only due to the availability and quality of food but also because of the heterogeneity in physical and chemical properties of the habitat (nodules and superfi cial sediment). Studies undertaken at the local scale (1 -5 km in distance) with the manned submersible Nautile showed for the fi rst time that nodule fi elds constitute a distinct habitat for infaunal communities, and that macrofauna and meiofauna components differ in abundance depending on the presence of nodules (Miljutina et al 2009 ).…”
Section: Diversity Of a Byssal B Enthosmentioning
confidence: 99%